Transformasi Organisasi: Peran Vital Kepemimpinan dalam Pengembangan Organisasi IPPNU di Desa Durung Bedug Sidoarjo yang Berkelanjutan - Anas Khatori; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2024)
This research discusses the vital role of leadership in the transformation of the IPPNU (Ikatan Putra - Putri Nahdlatul Ulama) organization in Durung Bedug Village, Sidoarjo, which aims for sustainable organizational development. The research method used is qualitative analysis through observation, interviews, and document analysis to explore the impact and effectiveness of leadership in driving positive changes in organizational structure and work culture. The findings show that the vital role of leadership becomes a key factor in facilitating collaboration, innovation, and commitment of members to achieve organizational goals. Adaptive and inclusive leadership has driven significant transformation within IPPNU, creating an enabling environment for sustainable growth. This research provides insight into the importance of the vital role of leadership in steering the organization toward sustainable development. The implications of this research involve the need for further recognition of the type of leadership that supports positive and sustainable change in the context of religious organizations such as IPPNU. In conclusion, the vital role of leadership is essential in stimulating the growth of an organization that is adaptive and relevant amidst the changing times.